Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Pendekatan Scientific - Linda Safitri; Yunisrul Yunisrul (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research used was Classroom Action Research (CAR). The purpose of this study was to describe the increase in student learning outcomes in integrated thematic learning using Scientific approach  in class III SD Negeri 05 Puhun Pintu Kabun. The research subjects were teachers (practitioners) and 29 students. The research location is SD Negeri 05 Puhun Pintu Kabun. . The results showed an increase in: a) RPP observation of the first cycle was 86,1 (B)%, the second cycle was 97,2% (A);b) Observation aspect of the first cycle teacher is 84,37% (B), the second cycle is 96% (A); c) Observation aspects of the student's first cycle is 82,81% (B) and the second cycle is 93,7% (A);d) learning outcomes in the first cycle are 75,38 (C) and the second cycle is 84,27 (B).